Rediscovery of Isonandra villosa Wight (Sapotaceae) - a Critically Endangered Species - Balasubramanian, P.; Murugesan, M. (Indian Forester, 2010)
The present paper highlights the rediscovery of a less known endemic, critically endangered and IUCN red-listed species, Isonandra villosa Wight (SAPOTACEAE) from Dhimbam Ghats in Eastern Ghats/Tamil Nadu after a lapse of 85 years. The present collection forms the rediscovery and also shows extension of its known rangeof distribution.